Pelatihan Penjualan Menggunakan E-Commerce Dalam Situasi Pandemi Covid-19 Di UMKM Kelurahan Sukajaya - Putri , Andini Utari; Meiriasari, Vhika; Hakim, Faradillah (Jurnal Abdimas Musi Charitas, 2021)
With the existence of e-commerce, it is very helpful in terms of sales and also the ease of purchasing transactions for sellers considering this unsupportive situation. People must also be smart in using information technology in order to survive or rise from the difficulties they face. Sales also increased with the e-commerce of several available applications. This community service activity aims to provide training on sales using e-commerce in order to increase sales during the current COVID-19 pandemic. This activity is aimed at MSMEs in the Sukajaya Village area with a maximum of 15 participants. However, what was given to visit only 12 participants for a period of more than 1 month was given for training given after evaluation of progress in 2 visits (31 August-28 September 2021). The visit was in the form of providing training materials which were given 2 times. The main obstacle is the limited knowledge of participants for some participants regarding the usefulness of e-commerce and its application. The results of this activity after being given training they are interested in using e-commerce as their tool to promote sales and also help them increase sales by using e-commerce.